Comparison of Sound Absorption Coefficient on Natural Fiber and Recycle Materials Panel - Azhar, Imran Asyraf; Mohd Sari, Kamarul Aini (Progress in Engineering Application and Technology, 2021)
Nowadays, there are various types of natural fiber produced to applied as sound absorption panel. These natural material-based panels have a lot of competition with synthetic materials. The absorbent material in the sound absorption panel is an important material to reduce noise production. The objective of this study is to identify past research on natural fiber expansion based on acoustic panels, to analyze Sound Absorption Coefficient (SAC) data at low frequency (1000 Hz) as well as to compare the best results. There are natural fibers such as coconut fiber, kapok fiber, rice husk fiber, sugarcane bagasse, wheat straw fiber, palm oil frond, wool fiber and coir while the recycle material are shredded paper, sawdust, crumb rubber, eucalyptus globulus leave, natural rubber, recycle paper and recycle rubber. The parameter studied is the value of the sound absorption coefficient at low frequency are density and thickness. The parameters referred to in this study are data from previous researchers related to the test of impedance tubes to obtain the value of sound absorption coefficient. This study is for a comparison of acoustic panels based on natural fibers and recycled materials. The results show palm oil frond with natural rubber has the highest sound absorption coefficient which is 0.96 compare to other materials. The thickness of an acoustic panel made of palm oil frond with natural rubber also the thickest which is 50 mm while the density is 350 kg/m3. There is a relationship between sound absorption coefficient and thickness and also density. The higher the sound absorption coefficient, the higher the thickness and the higher the density. The results encourage that natural fiber is good sound absorption material and still capable to be used as acoustic panel.